A Li–Al–O Solid‐State Electrolyte with High Ionic Conductivity and Good Capability to Protect Li Anode. (18th December 2019) - Xie, Meilan; Lin, Xing; Huang, Zhimei; Li, Yuyu; Zhong, Yun; Cheng, Zexiao; Yuan, Lixia; Shen, Yue; Lu, Xing; Zhai, Tianyou; Huang, Yunhui
Abstract: Using a solid‐state electrolyte (SSE) to stabilize the Li metal anode is widely considered a promising route to develop next‐generation high energy density lithium batteries. Here, a new polycrystalline aluminate‐based SSE (named Li–Al–O SSE) with good capability is introduced to protect Li metal. The SSE is formed on the Li metal surface via a chemical reaction between LiOH and triethylaluminum (TEAL) with the existence of LiTFSI‐based electrolyte. It is a continuous film that consists of polycrystalline LiAlO2, Li3 AlO3, Al2 O3, Li2 CO3, LiF, and some organic compounds. Such Li–Al–O SSE possesses a room‐temperature ionic conductivity as high as 1.42 × 10 −4 S cm −1 . Meanwhile, it effectively protects the Li anode from the corrosion of H2 O, O2, and organic solvent, and suppresses the growth of Li dendrite. With the protection of the Li–Al–O SSE, the cycle life of Li|Li symmetric cell and Li|O2 cell is substantially elongated, indicating that the SSE exhibits an excellent protective effect under both inert and oxidizing circumstances. Abstract : A new aluminate‐based solid‐state electrolyte is fabricated via a chemical reaction between LiOH and triethylaluminum in the presence of LiTFSI‐containing electrolyte. The aluminate‐based solid‐state electrolyte exhibits high ionic conductivity and good capability to stabilize Li anode in both inert and oxidizing conditions.